Statistical Convergence of Double Sequences of Order (?)over-tilde - Colak, R.; Altin, Y. (Hindawi Ltd, 2013)
We intend to make a new approach and introduce the concepts of statistical convergence of order (alpha) over tilde and strongly p-Cesaro summability of order (alpha) over tilde for double sequences of complex or real numbers. Also, some relations between the statistical convergence of order (alpha) over tilde and strong p-Cesaro summability of order (alpha) over tilde are given.
Keywords: Spaces